Differentiated approach to physical education of adolescents with different speed of biological development - Sitovskyi, Andrii; Maksymchuk, Borys; Kuzmenko, Vasyl; Nosko, Yuliya; Korytko, Zoryana; Bahinska, Olga; Marchenko, Oksana; Nikolaienko, Valerii; Matviichuk, Tetiana; Solovyov, Valeriy; Khurtenko, Oksana; Slyusarenko, Nina; et al. (Publicher University of Piteşti, 2019)
Aim: to justify and experimentally verify themethodology of differentiated approach to developing motor skills of seventh-graders depending on paces of their biological development. Material: 304 schoolchildren (148 boys and 156 girls), seventh-graders from the general education school No 20 in Lutsk, participated in the formative pedagogical experiment. The control group consisted of 99 boys and 105 girls and the experimental group – 49 boys and 51 girls, who were classified into the main medical group for health reasons and were not involved in sports sections. Results: It was found that schoolchildren with different levels of biological development within one age-sex group differ significantly in terms of the cardiorespiratory system capacity, physical performance and physical fitness. Therefore, the authors designed the methodology for allocating educational time to develop motor skills of seventh-graders during physical education lessons depending on paces of their biological development under the conditions of three physical education lessons per week. Conclusions: this methodology of differentiated approach to allocating educational time to develop motor skills of seventh-graders is an effective means for differentiated physical education of adolescents, which is reflected in the increase in the level of physical fitness and performance in seventh-graders during the pedagogical experiment.
Keywords: motor skills; quantitative estimation of biological age; differentiated physical training; differentiated assessment of physical fitness